Resistance Training to Failure vs. Not to Failure: Acute and Delayed Markers of Mechanical, Neuromuscular, and Biochemical Fatigue. Issue 4 (April 2021) - González-Hernández, Jorge M.; García-Ramos, Amador; Colomer-Poveda, David; Tvarijonaviciute, Asta; Cerón, José; Jiménez-Reyes, Pedro; Márquez, Gonzalo
Abstract : Abstract: González-Hernández, JM, García-Ramos, A, Colomer-Poveda, D, Tvarijonaviciute, A, Cerón, J, Jiménez-Reyes, P, and Márquez, G. Resistance training to failure vs. not to failure: acute and delayed markers of mechanical, neuromuscular, and biochemical fatigue. J Strength Cond Res 35(4): 886–893, 2021—This study aimed to compare acute and delayed markers of mechanical, neuromuscular, and biochemical fatigue between resistance training sessions leading to or not to failure. Twelve resistance-trained men completed 2 sessions that consisted of 6 sets of the full-squat exercise performed against the 10 repetitions maximum load. In a randomized order, in one session the sets were performed to failure and in the other session the sets were not performed to failure (5 repetitions per set). Mechanical fatigue was quantified through the recording of the mean velocity during all repetitions. The neuromuscular function of the knee extensors was assessed through a maximal voluntary contraction and the twitch interpolation technique before training, immediately after each set, and 1, 24, and 48 hours post-training. Serum creatine kinase (CK) and aspartate aminotransferase (AST) were measured before training and 1, 24, and 48 hours post-training to infer muscle damage. Alpha was set at a level of 0.05. A higher velocity loss between sets was observed during the failure protocol (−21.7%) compared with the nonfailure protocol (−3.5%). The markers of peripheral fatigue were generally higher and long lasting for the failure protocol. However, the central fatigue assessed by the voluntary activation was comparable for both protocols and remained depressed up to 48 hours post-training. The concentrations of CK and AST were higher after the failure protocol revealing higher muscle damage compared with the nonfailure protocol. These results support the nonfailure protocol to reduce peripheral fatigue and muscle damage, whereas the central fatigue does not seem to be affected by the set configuration.